Experimental investigation of the braking process of automobiles - Sokolovskij, Edgar (Transport, 2005)
The present article depicts the results of investigation of the braking parameters of automobiles equipped with ABS and without ABS. The values of the automobile deceleration, the increase of the deceleration time and the time of disbraking while braking on a dry asphalt‐concrete surface which was fixed in the course of the experimental investigation are presented. The dependence of deceleration of automobiles equipped with ABS and without ABS upon the primary driving speed is reflected and substantiated. The results of the investigation of braking of automobiles equipped with ABS and without ABS under winter conditions, i.e. on ice and snow are presented.First Published Online: 27 Oct 2010